2013
DOI: 10.1155/2013/180516
|View full text |Cite
|
Sign up to set email alerts
|

MHD-Conjugate Free Convection from an Isothermal Horizontal Circular Cylinder with Joule Heating and Heat Generation

Abstract: The present work is devoted to the numerical study of laminar magnetohydrodynamic (MHD) conjugate natural convection flow from a horizontal circular cylinder taking into account Joule heating and internal heat generation. The governing equations and the associated boundary conditions for this analysis are made nondimensional forms using a set of dimensionless variables. Thus, the nondimensional governing equations are solved numerically using finite difference method with Keller box scheme. Numerical outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…x  The step size of [18], Nazar [22], Molla [24], Azim and Chowdhury [26] and Mohamed [29], who applied the Keller-box method in solving the free convection flow of viscous, micropolar and nanofluid. A proper match among the comparative values of both tables has manifestly validated the present results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…x  The step size of [18], Nazar [22], Molla [24], Azim and Chowdhury [26] and Mohamed [29], who applied the Keller-box method in solving the free convection flow of viscous, micropolar and nanofluid. A proper match among the comparative values of both tables has manifestly validated the present results.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that for increasing Prandtl number values, the velocity and temperature profiles were both reduced at the lower stagnation region. The combined effects of MHD, joule heating and heat generation were then presented by Azim and Chowdhury [26] on free convection flow of a viscous fluid with convective boundary conditions. With the help of Keller-box method, they noted that the skin friction along the surface of the cylinder decreases with increasing magnetic parameter and conjugate conduction parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Natural convection studies with linear heat generation in fluid flow are of significant importance in solving several technological and physical problems. These studies have also attracted a significant research audience (Molla et al, 2006, 2009, Cheng, 2009, Kasim et al, 2011, Azim and Chowdhury, 2013, Zainuddin et al, 2016, Adeniyan et al, 2021, Opadiran, 2021. However, there are limited studies on the natural convection boundary layer flow with constant or inhomogeneous material properties around a horizontal cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been performed on magnetic field and heat generation effects on magnetohydrodynamic (MHD)-conjugate heat transfer. Azim and Chowdhury [11] investigated MHD-conjugate free convection from an isothermal horizontal circular cylinder with Joule heating and heat generation in the presence of a magnetic field. Azim et al [12] studied the problem of steady CHT through an electrically-conducting fluid for a vertical flat plate with a transverse uniform magnetic field.…”
Section: Introductionmentioning
confidence: 99%